2021
DOI: 10.1108/pm-08-2020-0051
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing real estate graduates soft skill gap in Nigeria

Abstract: PurposeThe purpose of this study is to evaluate the soft skill gap of graduate employees, as well as the factors influencing the skill gaps of real estate graduates in the employment of real estate firms in Nigeria.Design/methodology/approachPrimary data were employed for the study. Close-ended questionnaire served on real estate employers in the two major property markets of Nigeria: Lagos and Abuja. From a total of 343 questionnaires administered, 172 (59.7%) questionnaires were retrieved. While data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 27 publications
(29 reference statements)
1
18
0
1
Order By: Relevance
“…E.g. the subject-specific skills gaps, similar to our practical knowledge and its application , are evident in 35% of respondents from Guàrdia et al ( 2021 ), while the study by Ayodele et al ( 2021 ) indicated skill gaps in leadership, from students’ point of view. Our critical thinking and reasoning are similar to logical thinking and dispute resolutions, which are recognized by employers as skills with influenced gap (Ayodele et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…E.g. the subject-specific skills gaps, similar to our practical knowledge and its application , are evident in 35% of respondents from Guàrdia et al ( 2021 ), while the study by Ayodele et al ( 2021 ) indicated skill gaps in leadership, from students’ point of view. Our critical thinking and reasoning are similar to logical thinking and dispute resolutions, which are recognized by employers as skills with influenced gap (Ayodele et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…‘Competence gap’ is usually defined as a difference between the level of competence acquired during studies and the level of competence required in the workplace (demand). The gap can be observed from the perspective of different stakeholders — students (Nghia, 2018 ), graduates (Ayodele et al, 2021 ; Nghia, 2018 ), employers (Ayodele et al, 2021 ; Collet et al, 2015 ), and others, including e.g. academic staff and public sector (Guàrdia et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations